Profile of Dengue Fever Complication in Infant at Tertiary Referral Hospital in East Java, Indonesia - Khen Mikhael; Dominicus Husada; Pudji Lestari (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2022)
Introduction: Dengue virus infection is caused by the dengue virus and transmitted through the bites of infected Aedes aegypti or Aedes albopictus mosquitoes. The spectrum of clinical manifestations is varied from asymptomatic, undifferentiated fever, dengue fever, dengue hemorrhagic fever, dengue shock syndrome, to expanded dengue syndrome. Data from 2016 in Indonesia revealed that dengue virus infection is common in the population, with a total of 333.821 cases of dengue hemorrhagic fever. Methods: This was a descriptive study with a cross-sectional design. The subjects in this study were children under 1-year-old, diagnosed with dengue virus infection, and had a complication. The number of subjects used is 60 infants. Results: Infection of dengue virus in infants is often found in the 7-9 month age group (36,6%). Clinical manifestations found were fever (100%), vomiting (62%), diarrhea (43%), petechiae (22%), bleeding (12%), and irritable (5%). Thrombocytopenia and leukopenia were found in 93,3% and 26,6% of infants respectively. Complications were found in the form of pleural effusion (66%), hypoalbuminemia (62%), hyponatremia (51%), liver involvement (49%), hypocalcemia (43%), hypokalemia (23%), bleeding (21%), brain involvement (21%), kidney involvement (13%), and ascites (11%).Conclusion: The most common clinical manifestations are fever, diarrhea, and vomiting, while the most common complications are pleural effusion, hypoalbuminemia, hyponatremia, liver involvement, and hypocalcemia.